The Influence of Financial Literacy and Financial Recording on SMEs Performance In Lamongan - Pratama, Kartika Apriliani; Kautsar, Achmad; Indarwati, Tias Andarini (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
East Java Province is one of the provinces that has the largest number of MSMEs in Lamongan. If seen from two factors (internal and external), its development is still experiencing various obstacles in efforts to improve its performance, especially in small industries. The aim of this research is to find out how financial literacy and financial recording influence the performance of SMEs in Lamongan. This research is a type of causality research using quantitative methods. The data obtained came from the results of a questionnaire and was analyzed using SPSS. This research uses primary data sources and uses saturated sample sampling. The research results show that financial literacy is not significant, while financial recording has a significant positive effect.